Factors that cause mathematics anxiety among undergraduates students - Nur A'ain, Sabri (Universiti Malaysia Sarawak, UNIMAS, 2009)
This research investigated the factors that cause mathematics anxiety among undergraduate students by determined the greatest influence in the development of mathematics anxiety such as parents, teachers, society and peers. Grade level at which anxiety started and students’ perception about society beliefs and myths were also considered as contributory factors of mathematics anxiety. Besides, teaching strategies that could contribute and reduce mathematics anxiety were investigated. The research investigated relationships between all of these factors with mathematics anxiety. Seventy-three undergraduate students fr om the Cognitive Sciences Program in the Faculty of Cognitive Sciences and Human Development at University of Malaysia Sarawak were the sample for this study.The questionnaire from the previous researcher, Shields (2006)and Mathematics Anxiety Rating Scale –Short Version (MARS-S) was used as the research instrument in this study. The total score from the scale determined the level of mathematics anxiety. Besides, students’ perceived level of mathematics anxiety based on a one-question rating was also examined. Then, relationships between both mathematics anxiety levels were investigated using Pearson-product moment correlations. The results showed positive relationships between students’ perception about society mathematics myths and mathematics anxiety. In addition, the results also indicated relationships between the teaching strategies of individual, partner and team work activities in contributing to mathematics anxiety. In contrast, no relationships existed between teaching strategies posed to be ableto reduce mathematics anxiety with mathematics anxiety level. Grade level at which anxiety started and students’ perception about the importance of mathematics from the society showed insignificant relationship with mathematics anxiety. However, students’ perceived level of mathematics anxiety correlated positively with mathematics anxiety score, as measured on MARS-S.